2023
DOI: 10.37496/rbz5220220079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microencapsulated carvacrol and cinnamaldehyde on feed digestibility, intestinal mucosa, and biochemical and antioxidant parameters in broilers

Abstract: The objective of this study was to evaluate the effects of different levels of microencapsulated carvacrol and cinnamaldehyde on metabolizable energy, feed digestibility, intestinal morphometric analysis, and antioxidant parameters in broilers. A completely randomized design with five treatments and eight replications of eight broilers (Cobb male) was used, and collections were carried out at 20 and 42 days of age. Carvacrol and cinnamaldehyde concentrations (mg/kg) were: 0 (control), 50, 100, 150, and 200. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Puvača et al (2016) observed that Piper nigrum and Capsicum annuum supplementation for broiler chickens reduced lipid peroxidation in the liver and meat because of their antioxidant properties. Facchi et al (2023) observed that supplementation of 100 and 150 mg/mg microencapsulated carvacrol and cinnamaldehyde in diets of broilers at 20 days resulted in lower serum levels of TBARS and ROS. Karadas et al (2014) found that supplementation with a blend composed of 5% carvacrol, 3% cinnamaldehyde, and 2% capsicum oleoresin increased the retention of carotenoids in the liver and coenzyme Q10, which have antioxidant activity.…”
Section: Discussionmentioning
confidence: 93%
“…Puvača et al (2016) observed that Piper nigrum and Capsicum annuum supplementation for broiler chickens reduced lipid peroxidation in the liver and meat because of their antioxidant properties. Facchi et al (2023) observed that supplementation of 100 and 150 mg/mg microencapsulated carvacrol and cinnamaldehyde in diets of broilers at 20 days resulted in lower serum levels of TBARS and ROS. Karadas et al (2014) found that supplementation with a blend composed of 5% carvacrol, 3% cinnamaldehyde, and 2% capsicum oleoresin increased the retention of carotenoids in the liver and coenzyme Q10, which have antioxidant activity.…”
Section: Discussionmentioning
confidence: 93%
“…Robust research has been done regarding the use of feed additives to improve the performance of farm animals (Gois et al, 2023). The use of microencapsulated carvacrol and cinnamaldehyde can influence in the metabolizability of nutrients, increasing metabolizable energy in broilers (Facchi et al, 2023). Fish and sacha inchi oils (oil mixture), selenium yeast, and chromium yeast in hen feed increase egg production and decrease feed conversion (Morales-Suárez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%